Socio-political goals and responses to the reconstruction of the Chilean city of Constitución - Romero, Hugo; Albornoz, Cristian (Disaster prevention and management, 2016)
The purpose of this paper is to discuss the political and economic objectives sought by the government of Chile to understand the characteristics of the reconstruction process for housing damaged by the earthquake and tsunami of 27 February 2010, contrasted with the opinions of the target communities, the instruments that were utilized and the generation of new vulnerabilities.
Gesehen am 04.05.2020